Masa Depan Partai Politik Islam di Kota Medan : (Dinamika Koalisi Dalam Pilkada Medan 2024) - Muthahhari, Murtheza; Sahrin, Abu (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2024)
Abstract: Low voter participation and the shifting strategic role of Islamic political parties in the Medan mayoral election reflect structural problems within local democracy. This study analyzes how coalition pragmatism and a political recruitment crisis create a cycle that systematically erodes public trust. Employing a qualitative methodology with a case study approach in Medan City, data were collected through in-depth interviews, observation, and document analysis. The findings reveal a